Pancalis: Android-based leaning media for early reading in new normal - Ali Mustadi; Octavian Muning Sayekti; Evy Nur Rochmah; Enny Zubaidah; Septia Sugiarsih; Kordula Mechthild Schulze (LPMPP Universitas Negeri Yogyakarta, 2022)
Early reading is an essential skill that is needed to be accelerated through application-based media. This study aims to develop Pancalis as a medium for the online teaching of early reading. This study used the Research and Development (RD) approach using the ADDIE model. The subjects were two experts as well as 18 teachers and five students of elementary schools. They were established using the purposive sampling technique. The data collection technique used questionnaires and scales. The data analysis used descriptive statistics. The results show that: 1) at the analysis stage through literature study, it can be concluded that Pancalis as an Android-based application is an alternative learning media for the teaching of early-reading; while the result of field study shows teachers and students need learning media for early reading that can accommodate distance learning; 2) at the design stage, the Pancalis as an Android-based application for early-reading has been produced; 3) while at the end of the development stage, an assessment was carried out through an expert validation scale and it was found that the Pancalis is very suitable for the teaching of early-reading; while the practicality response questionnaire of teachers and students shows that Pancalis is very practical to use.